On Path Laplacian Eigenvalues and Path Laplacian Energy of Graphs - Shridhar Chandrakant Patekar; Maruti Mukinda Shikare (Journal of New Theory)
We introduce the concept of Path Laplacian Matrix for a graph and explore the eigenvalues of this matrix. The eigenvalues of this matrix are called the path Laplacian eigenvalues of the graph. We investigate path Laplacian eigenvalues of some classes of graph. Several results concerning path Laplacian eigenvalues of graphs have been obtained.